Intraoral synechiae with cleft palate in an older child: A case report and review of literature - Keyur Mevada; Annavarapu Gopalakrishna (Wolters Kluwer Medknow Publications, 2016)
Oral synechiae also called intraoral bands or congenital alveolar synechiae are extremely rare. The patient is usually a neonate with difficulty in breathing and feeding. We report the case of a 4-year-old child brought to the hospital for cleft palate repair having no history of breathing or feeding difficulty other than what was attributed to the cleft palate.